Clinical outcomes in hospitalized patients with community-acquired pneumonia: A comprehensive analysis of associated factors - Deema Rahme; Hania Nakkash Chmaisse; Pascale Salameh (PLoS ONE, 2026)
Background Community-acquired pneumonia (CAP) remains a significant cause of hospitalization and mortality globally. Optimizing clinical outcomes in CAP depends heavily on timely, appropriate empiric antibiotic therapy. However, limited data from low- and middle-income countries hinder effective stewardship efforts. The study aims to assess clinical outcomes among hospitalized CAP patients in Lebanon and identify key factors associated with deterioration or death, with particular emphasis on the role of guideline-concordant empiric antibiotic prescribing. Methods A cross-sectional study was conducted in five tertiary hospitals across Lebanon between January and June 2024. Adult patients admitted with CAP were included. Demographic, clinical, laboratory, microbiological, and treatment data were extracted. Antibiotic regimens were evaluated for adherence to national CAP guidelines. Multivariable logistic regression was used to identify predictors of poor clinical outcomes, defined as ICU admission or in-hospital death. Results Inappropriate antibiotic selection (aOR=18.81, p<0.001) and dosing (aOR=1.78, p=0.027) were significantly associated with poor outcomes. Additional predictors included advanced age, congestive heart failure, coronary artery disease, elevated WBC, and CURB-65 scores ≥3. Conversely, patients with classical CAP presentations (e.g., wheezing, rales) were more likely to experience favorable outcomes. Conclusion Inappropriate empiric antibiotic prescribing significantly worsens clinical outcomes in hospitalized CAP patients. These findings underscore the urgent need for strengthening antimicrobial stewardship programs, implementing clinical decision support tools, and reinforcing physician education to promote adherence to national guidelines and improve patient safety.